2021
DOI: 10.3390/life11090925
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Immune Function-Related Subtypes in Cutaneous Melanoma

Abstract: Tumour immunotherapy combined with molecular typing is a new therapy to help select patients. However, molecular typing algorithms related to tumour immune function have not been thoroughly explored. We herein proposed a single sample immune signature network (SING) method to identify new immune function-related subtypes of cutaneous melanoma of the skin. A sample-specific network and tumour microenvironment were constructed based on the immune annotation of cutaneous melanoma samples. Then, the differences an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 61 publications
0
2
0
Order By: Relevance
“…Wide exploratory studies addressing the immune aspects of melanoma TME were mostly solely computational [43][44][45], yet often meticulous and conclusive. The conventional and more supervised approaches, like ours, taking advantage of publicly available transcriptomic datasets also existed [46,47]; however, they usually carried different subtype annotations for what we believe could be recognized as immune desert, excluded, and inflamed tumors based on their biological information. Reports adopting the desert, excluded, inflamed nomenclature in melanoma were only histology based [48][49][50].…”
Section: Discussionmentioning
confidence: 99%
“…Wide exploratory studies addressing the immune aspects of melanoma TME were mostly solely computational [43][44][45], yet often meticulous and conclusive. The conventional and more supervised approaches, like ours, taking advantage of publicly available transcriptomic datasets also existed [46,47]; however, they usually carried different subtype annotations for what we believe could be recognized as immune desert, excluded, and inflamed tumors based on their biological information. Reports adopting the desert, excluded, inflamed nomenclature in melanoma were only histology based [48][49][50].…”
Section: Discussionmentioning
confidence: 99%
“…Up to now, some works have been carried out on molecular typing of cutaneous melanoma. Liu et al [9] proposed a single-sample immune signature network and identified an immune-related subtype based on hierarchical clustering of transcriptome data. The immune-related subtype were further subdivided into three subtype, one of which have the highest degree of immune infiltration and generally have better outcomes after immunotherapy.…”
Section: Introductionmentioning
confidence: 99%